2020
DOI: 10.1111/ppc.12624
|View full text |Cite
|
Sign up to set email alerts
|

The relationship between cyberloafing levels and social media addiction among nursing students

Abstract: The study was conducted to examine the relationship between cyberloafing levels and social media addiction among nursing students in different cities (Erzurum, Istanbul, and Van) in Turkey.Design and Methods: This study was comparative and descriptive in design, and the sample included 518 nursing students. Findings:The average Cyberloafing Scale (CLS) total score of the students was 87.71 ± 18.55, while the average Social Media Addiction Scale (SMAS) total score was 71.30 ± 19.85. A positive and moderately s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 23 publications
0
10
0
Order By: Relevance
“…One study found that nurses in Turkey were also affected by SMA ( Hosgor et al, 2021 ), but there were no studies in the physician population for reference. In addition, many studies in college students found that the incidence of SMA was already higher among medical staff during their school years ( Turan et al, 2021 ; Yilmazel, 2021 ; Ilter and Ovayolu, 2022 ). The scores for mood modification (3.210 ± 1.048) and tolerance (3.231 ± 1.197) were the highest, indicating that medical care professionals mainly use social media to avoid work problems and relieve anxiety and depression.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…One study found that nurses in Turkey were also affected by SMA ( Hosgor et al, 2021 ), but there were no studies in the physician population for reference. In addition, many studies in college students found that the incidence of SMA was already higher among medical staff during their school years ( Turan et al, 2021 ; Yilmazel, 2021 ; Ilter and Ovayolu, 2022 ). The scores for mood modification (3.210 ± 1.048) and tolerance (3.231 ± 1.197) were the highest, indicating that medical care professionals mainly use social media to avoid work problems and relieve anxiety and depression.…”
Section: Discussionmentioning
confidence: 99%
“…In recent years, most of the studies on social media addiction focus on college students and adolescents Li et al, 2018 , 2019 , 2020 ; Liu and Ma, 2018 ; Nie et al, 2019 ; Chen I. H. et al, 2020 ; Wang et al, 2020 ; Hu et al, 2021 ). There are only a few studies on medical students, nursing students ( Unal Aslan and Tar, 2021 ) and nurses ( Turan et al, 2021 ) around the world. The first theoretical advance of this study is to extend the study of SMA to the entire medical care professionals community.…”
Section: Theoretical Implicationsmentioning
confidence: 99%
See 2 more Smart Citations
“…Hospital managers need to ensure that these behaviors remain at a level that does not impair the productivity and attention of their employees (Turan et al, 2021). This validated SC scale could be used to assess SC behaviors of healthcare staff in Turkey.…”
Section: Discussionmentioning
confidence: 99%